A promise fulfilled Elia Costandi Nuqul and his business odyssey - Wheatcroft, Andrew; Hawatmeh, Christina Zacharia (I.B. Tauris, 2008)
Growing up in the ancient town of Ramleh, Elia Nuqul's sole ambition was to be an engineer. This book explores Elia Nuqul's life and demonstrates how his core values of loyalty, innovation and attention to detail lie at the heart of a family company which stands as an example throughout the Middle East and beyond.